The transcriptome of the veiled chameleon (Chamaeleo calyptratus): A resource for studying the evolution and development of vertebrates. Issue 8 (25th March 2019) - Pinto, Brendan J.; Card, Daren C.; Castoe, Todd A.; Diaz, Raul E.; Nielsen, Stuart V.; Trainor, Paul A.; Gamble, Tony
Abstract: Purpose: The veiled chameleon ( Chamaeleo calyptratus ) is an emerging model system for studying functional morphology and evolutionary developmental biology (evo‐devo). Chameleons possess body plans that are highly adapted to an arboreal life style, featuring laterally compressed bodies, split hands/ft for grasping, a projectile tongue, turreted independently moving eyes, and a prehensile tail. Despite being one of the most phenotypically divergent clades of tetrapods, genomic resources for chameleons are severely lacking. Methods: To address this lack of resources, we used RNAseq to generate 288 million raw Illumina sequence reads from four adult tissues (male and female eyes and gonads) and whole embryos at three distinct developmental stages. We used these data to assemble a largely complete de novo transcriptome consisting of only 82 952 transcripts. In addition, a majority of assembled transcripts (67%) were successfully annotated. Results: We then demonstrated the utility of these data in the context of studying visual system evolution by examining the content of veiled chameleon opsin genes to show that chameleons possess all five ancestral tetrapod opsins. Conclusion: We present this de novo, annotated, multi‐tissue transcriptome assembly for the Veiled Chameleon, Chamaeleo calyptratus, as a resource to address a range of evolutionary and developmental questions. The associated raw reads and final annotated transcriptome assembly are freely available for use on NCBI and Figshare, respectively. Key Findings: Transcriptome, developmental series, evolutionary developmental biology, lizard, visual evolution.